Students’ Techniques in Memorizing Vocabulary for Daily Conversation at PKP Al-Hidayah Jambi Boarding School - Mifthahul Nurzanah; Dzawil Hanifati Azizah; Rimarta Maharani (IJER (Indonesian Journal of Educational Research), 2023)
This study was aimed to investigating the students' technique in memorizing vocabulary and to identify the students' difficulties when technique in memorizing of vocabulary is done. This research is descriptive qualitative research. This study involved 9 students of Pkp Al-Hidayah Pal X Jambi to be participated. This research is concerning the students‘ technique in memorizing of vocabulary for their daily conversation of two dormitories The data were collected by interview and observation of the participants and analyzed descriptively. There are three sub-themes in the students' technique in memorizing vocabulary, two sub-themes in students' difficulties in memorizing new words, and a sub-theme of the result of each technique. There are three techniques used by students in memorizing vocabulary, which is English book use, saying the new words repeatedly, and naming the real object. While there are two possible students' difficulties in memorizing new words, which are Linguistics problems, and external and internal problems. Some suggestions are attached in the present study for a better improvement.